Strategies for Transparent and Accountable Management of Ramadan Social Aid Funds in Musholla - Rita Satria; Hadi Supratikta; Ruknan (CENDEKIA: Jurnal Pengabdian Masyarakat, 2025)
This community service project aims to enhance the transparency and accountability of Ramadan donation fund management at local mushollas. In many communities, religious institutions play a pivotal role in distributing social assistance, especially during the holy month of Ramadan. However, the absence of standardized financial governance often leads to inefficiencies and a lack of trust from the public. This program introduces structured financial management strategies, including documentation systems, transparent reporting mechanisms, and human resource training, to improve the effectiveness of social fund distribution. Through participatory workshops and practical tools, this initiative supports musholla administrators and volunteers in adopting accountable financial practices. The results indicate an increased awareness among committee members, improved documentation procedures, and more open communication with congregants regarding fund allocation. The success of this program underscores the importance of financial literacy and governance in maintaining the integrity of religious social activities.